EXAMINING THE REASONS AND POTENTIAL APPLICATIONS OF IOT TECHNOLOGY FOR THE HOTEL INDUSTRY IN BANGLADESH - Hossan, Farooq (International Journal of Business and Management Future, 2024)
With different industries, hospitality businesses stand to benefit significantly from the development of the Internet of Things (IoT). The research examines various potential applications for IoT, as well as the factors that led the hotel industry in Bangladesh to adopt the technology. The main issue raised by the statement of the problem is that Bangladeshi hotels need to integrate technology well, which results in poor service, dissatisfied customers, and inefficient operations. To give hotels a competitive edge in the market, this research aims to investigate how IoT can improve these areas. Examining scholarly publications, industry reports, and case studies about IoT technology in Hospitality, the study's main methodology was a literature review. With this method, the main drivers, obstacles, and possible uses of IoT in the Bangladeshi hotel sector were to be identified. The results emphasize that IoT can extensively improve guest experiences by enabling tailored services, enhancing security measures, and streamlining operations through automation. However, lack of technical expertise, challenges such as high execution costs, and concerns over data privacy were also identified. The key findings indicate that while the potential for IoT in the Bangladeshi hotel industry is extensive, successful accomplishment requires investment in infrastructure, strategic planning, and addressing the identified challenges. The study concludes with recommendations for policymakers and business stakeholders to advance IoT adoption, aiming to raise the standard of hospitality services in Bangladesh.JEL Classification Codes: L83, L86, R41, Z32, 014, 033.